Analisis Pengaruh Laba dan Arus Kas terhadap Financial Distress pada Perusahaan Transportasi yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016 - Cesty Calestia; Muhammad Roni Indarto (Telaah Bisnis, 2020)
Abstract This study aims to investigate the effect of Earnings Before Interest and Tax (EBIT) and cash flow on financial distress in transport companies listed on the Indonesia Stock Exchange in 2012 to 2016. Transportation in Indonesia began to show significant development after the attention given by the government through 13 logistical policies in 2015. The sample used in this study was 14 companies with 210 research objects. The results found evidence that EBIT and Cash Flow significantly influence financial distress.